2009
DOI: 10.1002/prot.22337
|View full text |Cite
|
Sign up to set email alerts
|

Conformational preferences of a short Aib/Ala‐based water‐soluble peptide as a function of temperature

Abstract: The amino acid Aib predisposes a peptide to be helical with context-dependent preference for either 3(10)- or alpha- or a mixed helical conformation. Short peptides also show an inherent tendency to be unfolded. To characterize helical and unfolded states adopted by water-soluble Aib-containing peptides, the conformational preference of Ac-Ala-Aib-Ala-Lys-Ala-Aib-Lys-Ala-Lys-Ala-Aib-Tyr-NH(2) was determined by CD, NMR and MD simulations as a function of temperature. Temperature-dependent CD data indicated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 30 publications
(72 citation statements)
references
References 57 publications
(110 reference statements)
3
69
0
Order By: Relevance
“…S2 Supplementary material), which might corroborate the role of the four residue segment 'L-G-K-Q' present at the N-terminus of CPS224Ac in recognition of sulfate ion. In aqueous solution, short peptides usually exist as conformational ensembles (Banerjee et al, 2009;Schweitzer-Stenner et al, 2007), however, for sulfate added species of CPS224Ac the observed increase in n-p* ($222 nm) band as well as the 'R-value' ([h] n-p* /[h] p-p* ) with decrease in temperature indicated the increment of helical population, with a preference towards predominantly a-helical form (Manning and Woody, 1991).…”
Section: Circular Dichroism and Ir Spectroscopymentioning
confidence: 83%
See 3 more Smart Citations
“…S2 Supplementary material), which might corroborate the role of the four residue segment 'L-G-K-Q' present at the N-terminus of CPS224Ac in recognition of sulfate ion. In aqueous solution, short peptides usually exist as conformational ensembles (Banerjee et al, 2009;Schweitzer-Stenner et al, 2007), however, for sulfate added species of CPS224Ac the observed increase in n-p* ($222 nm) band as well as the 'R-value' ([h] n-p* /[h] p-p* ) with decrease in temperature indicated the increment of helical population, with a preference towards predominantly a-helical form (Manning and Woody, 1991).…”
Section: Circular Dichroism and Ir Spectroscopymentioning
confidence: 83%
“…This might be either due to stabilization of helical conformation with change in helix-coil equilibrium towards helix or participation of non-helical residues in helix formation along with the stabilization of the existing helix. CD spectra of the model anchor helix (peptide ABGY in Banerjee and Basu (2002) and Banerjee et al (2009)) present at the C-terminus of the chimeric polypeptide CPS224Ac were also obtained in absence as well as in presence of sulfate ion separately. However, no appreciable change in CD spectra of ABGY were observed upon addition of sulfate ion ( Fig.…”
Section: Circular Dichroism and Ir Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations
“…4,30 Aib is sterically hindered by dialkylated side chains and thus its substitution generates a collapsed turn structure effectively. 34 Substituting Pro with Aib at position 8 and 11 causes 90% and 80% decreases in halo activity, respectively, as well as a 40% decrease in 5% shmoo assay compared to the native α-factor. Therefore, the dramatic reduction in activity strongly emphasizes critical role of the β-turn structures for pheromone activity.…”
Section: 1042mentioning
confidence: 99%